PERBANDINGAN ADEKUASI HEMODIALISIS BERDASARKAN AKSES VASKULAR PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA - Rensi Hepi Farenta (2022)
Background: Hemodialysis is a renal replacement therapy when the kidneys can no longer carry out the filtration process to remove metabolic waste contained in the blood. Before starting hemodialysis, it is necessary to provide effective vascular access to obtain adequate blood flow for adequate hemodialysis. Adequacy of hemodialysis can be measured quantitatively by calculating Kt/V or the ratio of urea clearance to the amount of urea distributed in the patient's body fluids during hemodialysis. Objective: To compare the adequacy of hemodialysis based on vascular access in chronic kidney disease patients undergoing hemodialysis. Methods: This study used a quantitative study with a cohort study design and analyzed using the Mann-Whitney test. The sampling method used purposive sampling for as many as 107 respondents with access to CVC/CDL (n=34), AVF/Cimino (n=73). The instrument used in this study was an observation sheet. Results: There was no difference in the adequacy of hemodialysis (Kt/V) based on vascular access used in chronic kidney disease patients undergoing hemodialysis (p-value 0,456 ; 0,438 ; 0,984). Both accesses can be applied to certain indications without causing concern for the patient because both accesses can still reach the target value of Kt/V. The frequency and duration of HD, Qb, and IDWG affect the value of Kt/V, while stable Qd doesn't affect Kt/V.